Europe's evolving graduate labour markets: supply, demand, underemployment and pay - Francis Green; Golo Henseke (Journal for Labour Market Research, 2021)
For most students the aspiration to gain employment in a graduate job is the main motivation for going to university. Whether they fulfil this aspiration depends considerably on national graduate labour markets. We analyse the comparative evolution of these markets across Europe over the decade leading up to 2015, focusing on supply, graduate/ high-skilled jobs, underemployment, wages, the graduate wage premium and the penalty for underemployment. The supply of tertiary graduates increased everywhere and converged, and this upward convergence is forecast to persist. In contrast the growth of graduate jobs was slower, not ubiquitous and nonconvergent. Underemployment was spreading, though at a modest rate; this rise was convergent but not ubiquitous. The rise was most substantial in Slovenia, Slovakia, the Czech Republic, Poland, Italy and Greece. Graduates' real wages trended predominantly downward, but varied a great deal between countries. The graduate wage premium declined by more than one percentage point in seven countries. Inferences are drawn for the formation of education policy, for the broader discourse on HE, and for research on graduate futures.
Keywords: I23; J2; J31; 330; Overeducation; Wage premium; Tertiary education; Social cohesion; Convergence